INTERAKSI SOSIAL PADA RANTAI PEMASARAN SUSU SEGAR - Kusumastuti, Anie Eka; Azizah, Siti (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2023)
This research was conducted in Bocek Village, Karangploso District, Malang Regency as one of the several village agribusiness centers for fresh milk around the KUD Karangploso area. The research purpose was to determine social interaction in the fresh milk marketing chain. The research method used was survey method. Type of data uses were primary data and secondary data. Primary data obtained through observation, direct interviews to dairy farmer and cooperative officer & Netle representative, and documentation. While secondary data obtained from relevant documents. The theoretical approach used was the social interaction theory which it can be consist of the form of cooperation, competition as well as conflict and accommodation. Data then analyzed descriptive qualitatively. In general, there are two main characteristics of social interaction, namely associative and dissociative. The results indicated that the social interaction that was formed in the marketing of fresh milk by dairy farmers in the Karangploso KUD area was social interaction between farmers because there was an organizational relationship between members of the Karangploso KUD. The social interaction of dairy farmers with the KUD Karangploso was formed due to cooperation in marketing fresh milk. While social interaction between KUD Karangploso and PT. Nestle Indonesia is in the form of cooperation in the distribution of fresh milk on the basis of contractual cooperation.